Ultrasonic Synthesis, Molecular Structure and Mechanistic Study of 1,3-Dipolar Cycloaddition Reaction of 1-Alkynylpyridinium-3-olate and Acetylene Derivatives - Aboelnaga, Asmaa (Molecules, 2016)
Regioselectively, ethyl propiolate reacted with 1-(propergyl)-pyridinium-3-olate to give two regioisomers; ethyl 4-oxo-8-(prop-2-ynyl)-8-aza-bicyclo(3.2.1)octa-2,6-diene-6-carboxylate 4, ethyl 2-oxo-8-(prop-2-ynyl)-8-aza-bicyclo(3.2.1)octa-3,6-diene-6-carboxylate 5 as well as ethyl 2,6-dihydro-6-(prop-2-ynyl)furo(2,3-c)pyridine-3-carboxylate 6. The obtained compounds were identified by their spectral (IR, mass and NMR) data. Moreover, DFT quantum chemical calculations were used to study the mechanism of the cycloaddition reaction. The regioselectivity was explained using transition state calculations, where the calculations agreed with the formation of products 4 and 5 in almost the same ratio. The reaction was also extended for diphenylaceylene as dipolarophile to give only two products instead of three.